Effect of Berry Weight and its Components on the Contents of Sugars and Anthocyanins of Three Varieties of Vitis vinifera L. under Different Water Supply Conditions - Ferrer, M.; Echeverría, G.; Carbonneau, A. (South African Journal of Enology and Viticulture, 2016)
The influence of berry size on wine quality is a matter of debate. With the aim to contribute to that debate, a study of the influence of the varieties Tannat, Merlot and Cabernet Sauvignon on berry weight, on berry components (flesh, seeds and skin) and on the varieties’ oenological potential under different water supply conditions was carried out in Uruguay between 2001 and 2004. Replicated samples of 250 berries per vineyard were gathered at technological maturity at harvest. Berry weight and volume, weight ratio among each of the components and anthocyanin potential (ApH1 ) were measured and a basic analysis of the must was carried out. The vine water status was established through the measurement of pre-dawn leaf water potential. The tests showed that berry weight and sugar content were positively correlated and depended on variety, as was evident from the proportions of the berry components. Flesh weight was the most important determinant of berry weight, and flesh weight changed with the weight of the seeds. Larger values of these two components explained the heavier berries of the Tannat variety. On the other hand, Tannat berries had higher contents and concentrations of anthocyanins and sugars, and displayed the largest variation in these chemical compounds. Berry weight, weight and proportion of skin or their relationships did not determine anthocyanin contents or concentration. In response to the years’ water conditions, different varieties showed different behaviours, explaining the variation in weight and in the composition of the berries.